Public Knowledge and Perception towards the Roles of Pharmacists in Health Care System: A Quantitative Survey Study - J, Subadradevi; S, Vishnupriya; A, Jasmine Fathima; M, Indhu Priyadarshini (Indian Journal of Pharmacy Practice)
Background: A pharmacist is an individual who involved in designing, manufacturing, dispensing, managing and planning of a pharmaceutical care plan. Inside a professional network of patients and pharmacists, pharmacists are expected more for providing pharmaceutical care. It’s commonly accepted that the public satisfaction is an essential part in the quality of health care. Unless the patients or public properly understand the professional roles of pharmacist related to patient care activities, the proper and better pharmaceutical care implementation cannot be attained. Aim: This survey was planned to conduct with the main aim to determine the knowledge and perception of society towards the roles, responsibilities along with various services provided by the pharmacists. Materials and Methods: Based on inclusion criteria 1000 people were included in this study. After giving their consent, survey questionnaires were answered by the people on their own. Results: In that majority of the people (45.2%) agreed and 22.9%. of people strongly agreed that the pharmacist having important role in health care system. Conclusion: This study represents that most of the people (45.2% + 22.6% = 68.1%) know the important roles of pharmacists and indicates that general public having positive perception and knowledge about the various roles of pharmacist in healthcare system.
Keywords: Pharmacist Perception; Knowledge; Health care system